2012
DOI: 10.1111/j.1469-7610.2012.02528.x
|View full text |Cite
|
Sign up to set email alerts
|

Universality of categorical perception deficit in developmental dyslexia: an investigation of Mandarin Chinese tones

Abstract: The behavioral and electrophysiological results demonstrate impaired categorical perception of lexical tones in Chinese children with dyslexia. Our findings support the hypothesis that children affected by dyslexia have a general deficit in categorical perception of speech, which generalizes to nonalphabetic languages at the suprasegmental level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 43 publications
5
81
1
Order By: Relevance
“…It is generally agreed that people can automatically process the stimuli without attention at the pre-attentive stage. Recent studies, in contrast to Luo et al (2006), have suggested that acoustic and phonological information may be processed at both attentive and pre-attentive stages in parallel (Xi et al, 2010;Zhang et al, 2012b). In the present study, we differentiated the acoustic and the phonological information with a more fine-grained level, especially with regard to the acoustic interval of the stimulus.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…It is generally agreed that people can automatically process the stimuli without attention at the pre-attentive stage. Recent studies, in contrast to Luo et al (2006), have suggested that acoustic and phonological information may be processed at both attentive and pre-attentive stages in parallel (Xi et al, 2010;Zhang et al, 2012b). In the present study, we differentiated the acoustic and the phonological information with a more fine-grained level, especially with regard to the acoustic interval of the stimulus.…”
Section: Discussionmentioning
confidence: 79%
“…For example, Zhang et al (2012b) found that Chinese-speaking children who were at risk for dyslexia showed no significant differences between the across-category vs. within-category stimuli, in contrast to both adults and agematched normally developing children. It could be that children with reading disorders may perceive the phonological information in the same way as they do with acoustic information.…”
Section: Introductionmentioning
confidence: 99%
“…Three articles were written in Brazil (4,12,19) , 3 in the Netherlands (20,23,25) , 3 in the United States (31,32,34) and 3 in France (26,29,30) . Studies have also been found in China (24,27) , Germany (33) , Canada (22) and Israel (37) . There was great variation in the size of the sample, from surveys with only 12 subjects (12) to surveys that included 110 individuals (38) .…”
Section: Resultsmentioning
confidence: 93%
“…The participants' ages ranged from 2 months (23) to 12 years of age (4,12,19,22,35,37) . Regarding the parameters used to perform the MMN, most of the research used the speech stimulus (4,(20)(21)(22)(23)(24)(25)(26)30,(32)(33)(34)(35)(36) and other studies opted to perform the MMN with tone burst stimulus (12,19,22,(27)(28)(29)31,(37)(38)(39) . Regarding the tone burst stimulus, it was verified that some studies evaluated with frequency variation (12,(27)(28)(29)31,(37)(38)(39) and 1, by duration and frequency (19) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation